Get the Right Tree Care Professional - Eliana Kampf; Astrid Delgado; Mary Duryea; Traci Partin; Edward Gilman (EDIS, 2007)
FOR-116, a 4-page full-color fact sheet by Eliana Kampf, Astrid Delgado, Mary Duryea, Traci Partin, and Edward Gilman, illustrates hurricane recovery situations which can be handled by the homeowner and which require the services of a tree care professional or arborist, and how to find a qualified arborist. Published as Chapter 2 of the Urban Forest Hurricane Recovery series of the UF School of Forest Resources and Conservation and Environmental Horticulture Department, January 2007.